In a graph the roots of the function are given by the cut points with the x axis.
On the other hand, we have the following equation:
y = -x2 - x + 6
To find the roots, we equate to zero:
-x2 - x + 6 = 0
Rewriting we have:
x2 + x - 6 = 0
(x-2) (x + 3) = 0
The roots are:
x1 = 2
x2 = -3
Answer:
The roots are:
x1 = 2
x2 = -3
Answer:
±5sqrt(2) =x
Step-by-step explanation:
65=15+x^2
Subtract 15 from each side
65-15=15-15+x^2
50 = x^2
Take the square root of each side
±sqrt(50) = sqrt(x^2)
±sqrt(25*2) =x
±sqrt(25)sqrt(2) =x
±5sqrt(2) =x
Three and one hundred forty one hundredths <span />
Answer:
What do we start a convo or an argumnet about...and why?
Step-by-step explanation:
but heres one : Donald Trump or Biden?
heheheheheheh
Answer:
See below.
Step-by-step explanation:
Either 3 packets of 6 pens or
2 packets of 9 pens.